Strategi dan Kesalahan Mahasiswa Prodi BSA dalam Menterjemahkan Naskah Berbahasa Indonesia ke Bahasa Arab - Dolla Sobari (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2018)
Translating is a language skill in transfering meanings or messages from a source language (SL) to a target language (TL) by considering lingustic aspects and the culture of its speakers. In translation activity, the transfered messages should not be different from those of the source language, thus the speakers of the target language are able to understand the meanings or massages received. The importance of translating Indonesian text into Arabic language involves providing information about Indonesian cultures such a way that people will be well informed of Indonesia in general. The subject of this study is the students majoring in Arabic language and literature, particularry those who are taking translation course. The problem of the study is concerned with translation applied by the students in translating Indonesian writtten texts Arabic language. The second problem of the study dealt with finding errors made by the students in translating the texts. The kind of this study is a field research. Speaking & listening methods were used to collect data. Meanwhile, descriptive qualitative technique was used to analyze data. The results of the study indicate that the translation strategies applied by the students in this research consist of transposition (8) form addiction (7), arabic formation (6), borrowing meanings (5), word reduction (4), deletion (2), narrowing (2) and using synonim (1). Then, the unused strategies in translating Ibnu Rusdy’ t texts concist of modulation, expansion, equvalence and transfer. in the meantime, the errors made by the students in translating the texts are in terms of semantic error, (6 times), phonological error (4 ), morphological error (8) and syntactical error (5). Key words : Strategies, error, translating.